Forest Composition, Fuelwood Harvest and Regeneration Status in Four Community Forests of Central Nepal - Subedi, Ghanashyam; Khatiwada, Binod; Bhattarai, Sandesh; Acharya, Kamal Prasad (Scientific World, 2010)
Present study aims to explore forest composition, fuelwood harvest and regeneration status in two community forests of central Nepal. We carried out our study in different periods of 2007 and 2008. Household surveys were conducted to find the condition of fuelwood harvest and people dependency on community forest. Community forests of Nawalparasi districts are dominated by Shorea robusta whereas community forests of Syanja district are dominated by Castanopsis indica and Schima wallichii with highest IVI value. Percapita fuelwood consumption and domestic animals are higher in Nawalparasi district than in Syanja district. Grasses are the main source of fodder in Nawalparasi district whereas trees in Syanja district. Farmland is the main source for fodder in both the districts but even higher in Syanja district. For fuelwood people depend on forest than the farmland. Dominant tree species in Patapati Lulpani Community Forest (PLCF) showed reverse J-shaped size class distribution indicating sustainable regeneration whereas dominant tree species in Gamtam Community Forest (GCF), Dhuseri Community Forest (DCF) and Bhedawari Community Forest (BCF) showed poor regeneration status. Key words: Community forest; Forest composition; Fuelwood harvest; Regeneration. DOI: 10.3126/sw.v7i7.3826 Scientific World Vol.7(7) 2009 pp.53-58